Curriculum Management Characteristics in Arabic Language (A Comparative Study of Curriculum Documents in Arabic Language Education at UINSI Samarinda and UIN FAS Bengkulu) - Ahmad Fadhel Syakir Hidayat; Akhirudin Akhirudin; Sutiah Sutiah (Lisanan Arabiya: Jurnal Pendidikan Bahasa Arab, 2023)
Curriculum documents should have appropriate characteristics to produce graduates in line with educational objectives, necessitating a thorough examination of an educational institution's curriculum documents. Therefore, the aim of this research is to investigate the curriculum management characteristics in Arabic language education at UINSI Samarinda and UIN FAS Bengkulu. This study adopts a qualitative approach, specifically a library research, utilizing primary data sources such as curriculum documents in Arabic language education at UINSI Samarinda and UIN FAS Bengkulu, as well as relevant secondary data sources such as books and journals. A systematic and ongoing data analysis is conducted, involving data reduction, data display, and conclusion stages. The research findings reveal that the curriculum management characteristics in Arabic language education at both campuses encompass a theological foundation, which is a distinctive feature of Arabic language education within the realm of Islamic educational management, as well as rational, empirical, and theoretical foundations.